Phenological and Agro-Morphological Traits of Selected Broad-Leaf Mustard Varieties of Nepal - Poudyal, Damodar; Poudyal, Prakriti; Acharya, Prakash; Shrestha, Gopal Prasad (Genetics, Plant Breeding and Seed Science, 2025)
An action research study was conducted in 2016 to characterize some of the major winter vegetables commonly cultivated in Nepal, focusing on three widely grown broad-leaf mustard (Brassica juncea var. rugosa) varieties: Khumal Rato Paat, Manakamana, and Khumal Chauda Paat. The objective was to document key phenological features and agronomic traits of these varieties under field conditions at Thankot, Kathmandu. The study recorded varietal differences in seedling traits, vegetative growth, floral attributes, and seed characteristics. Significant morphological and agronomic variations were observed among the varieties. Khumal Rato Paat featured dark green glossy leaves with deep serration and purple veins and was comparatively late to bolt. Manakamana matured early and produced the highest fresh leaf yield. Khumal Chauda Paat was intermediate in most traits but exhibited highly blistered leaves. These findings highlight distinct varietal traits that can support variety identification, seed quality control, and future breeding efforts in leafy mustard crops.